2020
DOI: 10.1021/acsaelm.9b00694
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Artificial Synapses Based on Two-Dimensional van der Waals Materials for Brain-Inspired Computing

Abstract: On the basis of recent research, brain-inspired parallel computing is considered as one of the most promising technologies for efficiently handling large amounts of informational data. In general, this type of parallel computing is called neuromorphic computing; it operates on the basis of hardware-neural-network (HW-NN) platforms consisting of numerous artificial synapses and neurons. Extensive research has been conducted to implement artificial synapses with characteristics required to ensure high-level perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 142 publications
0
114
0
Order By: Relevance
“…[ 14 ] As well as FETs, 2D materials have been utilized in non‐volatile memory (NVM) devices, which are one of key building blocks for modern integrated circuits. [ 15,16 ] In particular, lots of efforts have been devoted to floating gate (FG) type memory devices. Their device structures have also evolved from the early stage of MoS 2 channel/HfO 2 tunnel barrier/multilayer graphene FG [ 17 ] stacks to recent 2D hetero‐stack of WS 2 channel/ h ‐BN tunnel barrier/graphite FG, [ 18 ] where the large memory window over 20 V for gate voltage ( V G ) range of ± 25 V and a good retention characteristic of 13% charge loss after 10 years have been demonstrated.…”
Section: Figurementioning
confidence: 99%
“…[ 14 ] As well as FETs, 2D materials have been utilized in non‐volatile memory (NVM) devices, which are one of key building blocks for modern integrated circuits. [ 15,16 ] In particular, lots of efforts have been devoted to floating gate (FG) type memory devices. Their device structures have also evolved from the early stage of MoS 2 channel/HfO 2 tunnel barrier/multilayer graphene FG [ 17 ] stacks to recent 2D hetero‐stack of WS 2 channel/ h ‐BN tunnel barrier/graphite FG, [ 18 ] where the large memory window over 20 V for gate voltage ( V G ) range of ± 25 V and a good retention characteristic of 13% charge loss after 10 years have been demonstrated.…”
Section: Figurementioning
confidence: 99%
“…The operating energy for reading and updating a weight were approximately from 0.12 to 0.71 nJ (for reading energy) and 0.79 (for updating energy in the potentiation channel)/0.93 (for updating energy in the depression channel) pJ, respectively, where a spike with 1 V of amplitude and 10 ms of duration was applied 45 . Such dissipated energy per event were determined by P = I × V × t duration 12,16,18 , and relevant details are provided in Supplementary Fig. 14.…”
Section: Resultsmentioning
confidence: 99%
“…Woo et al and S. Park et al reported HfO x RRAM and AlO x /TiN PCMO-based synaptic devices, respectively, where the nonlinear and asymmetrical conductance change resulted in a low inference accuracy of <40% for the Modified National Institute of Standards and Technology (MNIST) dataset 26 , 27 . For the HfO x RRAM, an AlO x barrier layer was introduced, consequently improving its conductance change more linearly, but this device inherently presented low dynamic range and high CCV 18 , 26 . For the hafnium-zirconium oxide FeFET-type synapse reported by M. Jerry et al, a highly symmetric conductance change was achieved, leading to a high inference accuracy of 90% for the MNIST dataset 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the definition of presynaptic terminals to input stimuli, the synaptic devices based on these 2D materials can be categorized as transistor‐ or memristor‐type artificial synapses. [ 222,230,231 ] The former are usually three‐terminal devices that use electric/optical gates as presynaptic input terminals and 2D semiconductors with source–drain electrodes as the postsynaptic output terminal ( Figure a,b). [ 225 ] The source–drain current after a presynaptic input signal is defined as post‐synaptic current (PSC) (Figure 10c).…”
Section: Bioelectronic Devices Based On 2d Materials Beyond Graphenementioning
confidence: 99%